10 - The Political Economy of Terrorism: 10.4314/ad.v27i1.22158 - Amuwo, Adekunle (Africa Development, 2002)
This paper seeks to explicate the underlying structural factors that, over the past several decades, have made terrorism a more or less viable instrument of political change in an increasingly fractionalized global hamlet. Terrorism is, however, a multi- faceted phenomenon involving both a systematic and sporadic use of terror by governments and other social actors, with a view to forcing some specific or general political and related objectives. Using an implicit dialectical materialist methodology, the paper explores the international political economy anchored on an essentially Western frame of reference of interests and contradictory values that permits the US and its allies to run the globe as they deem fit-including using, misusing and abusing the rest of the world. Elements within this frame include violation of international laws; contempt for international treaties as well as for the UN when expedient to do so; selective application of democratic values and principles; support of strong-arm rulers/ tin-pot dictators when they are useful and their abandonment when their nuisance value diminishes. The paper argues that the rule of force as against the rule of law has tended to radicalize the victims, admittedly in varying degrees. It suggests in conclusion, the articulation, by all stakeholders in a shrinking global ecology, of a people- friendly and people-centred ethical compass, one apt at making inter-state, inter-national and inter-people relations more humane and more human. Enlightened self-interest ought to dictate to everyone concerned that it is in their common interest to assiduously work towards this goal.